Highly sensitive liquid level sensor using fiber braggs grating and graphene diaphragm - Odai Falah Ameen, 1975- 604635; Raja Kamarulzaman Raja Ibrahim, supervisor 297480; Muhammad Safwan Abd. Aziz, 1988-, supervisor 546754; Asrul Izam Azmi, supervisor 185626; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Fizik))